The Effect Of Strategic Planning, Innovation Capability, And Competitive Advantage On Business Sustainability - Zeanette T Lisbet; Abdul Hafid Burhami; Nurwahidah Mashuddin; Nur Asia Hamid (Journal Management & Economics Review (JUMPER), 2026)
This study looks into how strategic planning, innovation capability, and competitive advantage can affect business sustainability. With the increasingly competitive environment and changing times, companies have to put in place proper strategies and capabilities that will ensure their sustainability and future development. The current research uses a quantitative approach whereby the research is descriptive in nature and explores the interrelationships between the various factors. The data used in this study was collected from managers and owners of businesses through structured questionnaires and analyzed through multiple regression. It is established from this research that each of the three factors discussed has a significant impact on business sustainability. Competitive advantage appears to be the most influential factor in the whole process of sustainability for any organization in the modern environment. The research reveals that all these three factors have been significant in explaining business sustainability. Therefore, it can be concluded that in order to enjoy competitive advantage, organizations need to use strategic planning coupled with innovation efforts.